Forage intake by heifers on alexander grass (Urochloa plantaginea (Link.) Hitch) fertilized with different levels of nitrogen (Research, Society and Development, 2021)
This work was conducted to study the efficiency of using nitrogen on Alexander Grass (Urochloa plantaginea (Link.) Hitch) through information about the characteristics of the pasture and forage intake of beef heifers. The experiment was carried out at the Federal University of Santa Maria (Universidade Federal de Santa Maria, UFSM) in Santa Maria, Rio Grande do Sul, Brazil, from January to April of 2014. The treatments consisted of doses of zero, 150, or 300 kg/ ha nitrogen (N) in the form of urea. The study used a rotational pasture method and 16 Angus heifers with a mean initial age and body weight (BW) of 15 months and 276 ± 17.4 kg, respectively. Forage intake was evaluated by treating two picketed test heifers with chromium oxide (Cr2O3) for eleven days as an external indicator of fecal production. The experimental design was completely randomized, and the measurements were repeated over time with three treatments and two repetitions per area. Crude protein content was 3.4% higher under 300 kg/ha nitrogen fertilization compared to 150 kg/ ha (18.7%). Independent of the N application rate, the heifers ingested 2.2 ± 0.09 kg DM 100/ kg BW of forage. Nitrogen fertilization of Alexander grass modified the structure of the pasture, increasing the quality and total production of the forage. Heifers pastured on Alexander grass fertilized with 300 kg/ha nitrogen harvested forage with higher levels of crude protein. The structural change in the canopy let the heifers reduce their consumption of forage at the end of the Alexander grass life cycle.